Short-Term Radiographic Evaluation of a Tri-Tapered Femoral Stem in Direct Anterior Total Hip Arthroplasty - Messamore, William G. (Kans J Med, 2020)
INTRODUCTION: Direct anterior approach (DAA) total hip arthroplasty (THA) has become increasingly popular, largely due to utilization of a true internervous and intermuscular plane. However, recent literature has demonstrated an increased rate of femoral implant subsidence with this approach. Hence, different femoral implants, such as the tri-tapered femoral stem, have been developed to facilitate proper component insertion and positioning to prevent this femoral subsidence. The purpose of this study was to evaluate the subsidence rate of a tri-tapered femoral stem implanted utilizing a DAA, and to determine if the proximal femoral bone quality affects the rate of subsidence. METHODS: A retrospective analysis of 155 consecutive primary THAs performed by a single surgeon was conducted. Age, gender, primary diagnosis, and radiographic measurements of each subject were recorded. Radiological evaluations, such as bone quality, femoral canal fill, and implant subsidence, were measured on standardized anteroposterior (AP) and frog-leg lateral radiographs of the hip at 6-week and 6-month postoperative follow-up evaluations. RESULTS: The average subsidence of femoral stems was 1.18 ± 0.8 mm. There was no statistical difference in the amount of subsidence based on diagnosis or proximal femora quality. The tri-tapered stem design consistently filled the proximal canal with an average of 91.9 ± 4.9% fill. Subsidence was not significantly associated with age, canal flare index (CFI), or experience of the surgeon. CONCLUSION: THA utilizing the DAA with a tri-tapered femoral stem can achieve consistent and reliable fit regardless of proximal femoral bone quality.